Dynamic properties of inhomogeneous states in cuprates (Review Article) - Lorenzana, J.; Seibold, G. (Физика низких температур, 2006)
We review the static and dynamical properties of stripe textures with regard to their relevance
in high-Tc superconductors. Our investigations are based on the time-dependent Gutzwiller approximation
which allows for the computation of random-phase approximation-like (RPA) fluctuations
on top of the Gutzwiller approximation (GA). No restrictions are imposed on the charge and
spin configurations which makes the method suitable for the calculation of linear excitations
around symmetry-broken solutions. Within this approach we calculate the optical conductivity of
stripes and compare our results with reflectivity experiments on cuprates. Furtheron we use the
spin-rotational invariant extension of the GA + RPA method in order to investigate the characteristics
of magnetic excitations in the stripe phase of cuprates. Our results are in very good agreement
with neutron scattering and optical experiments on lanthanum cuprate superconductors.